Recurrence Rate in Aesthetic Approach for Removal of Epidermoid Cyst (Medical Forum Monthly, 2024)
Objectives: To determine the recurrence rate in minimally invasive aesthetic approach for removal of epidermoid cysts Study Design: Observational /descriptive study.Place and Duration of Study: This study was conducted at the Peoples University of Medical and Health Sciences Nawabshah (PUMHS) from October 2013 to October 2015.Materials and Methods: 125 cases with epidermoid cyst were included according to selection criteria. Procedures were performed in main operation theater under local anesthesia. A small stab incision, less than 5mm, given and cheesy contents of the cyst expressed out by squeezing lateral pressure with index finger and thumb. Wall of the cyst was stripped and squeezed out with artery forceps. Wounds were not stitched but approximated with adhesive dressing. patients were than sent home and three doses of oral amoxicillin with diclofenac sodium was prescribed in all cases. Follow up visits were scheduled to observe any post operative bleeding, wound infection, wound cosmetics and any recurrence.Results: Among 125 cases 82 were male and 43 were females with M:F ratio of 3:2. Mean age was 29 years with a range of13- 52 and SD ± 9. Mean operating time was 12 minutes with SD ± 3 and a range of 8-15. Primary hemorrhage was noted in 1(0.8%) reactionary bleeding was noted in 2(1.6%) while there was no any secondary bleeding. wound infection was noted in 4(2.4%) cases. Wound cosmetics was remarkable as scar was almost non visible after some time. There was no any recurrence even after 1 year follow up.Conclusion: Minimally invasive aesthetic approach to remove small epidermal cysts at cosmetically concern body areas, give excellent scar cosmetic and no greater chance of recurrence.